The Latin American Middle Class: Fragile After All? - Francesca Castellani; Gwenn Parent; Jannet Zentero (Inter-American Development Bank (IDB), 2014)
This paper joins in the debate on the size of the middle class in Latin America, providing an analysis of its structure and characteristics. Using several measurements, it finds that 40-60 percent of Latin American households are middle class, a share which has consolidated over the past decade. The analysis reveals that gender, age, and education are associated with the likelihood of being middle class. The example of Colombia illustrates that, while growing in size, this income group still faces deficits in crucial dimensions of well-being, such as education, job formality, and health care, which are generally associated with being middle class. The analysis reveals the fragility of this emerging group in the region.
hdl:11319/6733
Keywords: D3; I3; D6; 330; Middle class; Latin America; Multidimensional poverty